Exploring District-Wise Water Poverty in West Bengal through Geospatial Analysis: Aligning with SDG 6 (Prakriti - The International Multidisciplinary Research Journal, 2025)
Water scarcity is a concern in West Bengal, with large variations in availability to safe drinking water between districts. This study uses geospatial analysis to investigate district level water poverty in the state, in line with United Nations Sustainable Development Goal (SDG) 6, which seeks to provide universal access to clean water and sanitation. Data from the 2011 Census and the 2015-2016 National Family Health Survey (NFHS) were used to evaluate household access to drinking water, including distance to water sources and intake of untreated water. A composite Water Deprivation Index was created with standardized indicators and geographical inequality was assessed using Atkinson’s index and Moran’s I statistics. The study finds high regional variation in water availability, with minimal spatial autocorrelation indicating that water scarcity is driven less by geographical proximity and more by localized characteristics such as infrastructure, geography, and population density. The findings underline the importance of region-specific initiatives to promote water access, maintain sustainable water management, and alleviate water inequality.
Keywords: Drinking Water Deprivation; Explorative Spa tial Data Approach; Atkinson’s Inequality Index; Moran’s